Numerical confirmations of joint spike transitions in G2 cosmologies. (17th March 2022) - Lim, W C
Abstract: We produce numerical evidence that the joint spike transitions between Kasner eras of G 2 cosmologies are described by the non-orthogonally transitive G 2 spike solution. A new matching procedure is developed for this purpose.